Low-grade Glioma Surgery in Intraoperative Magnetic Resonance Imaging: Results of a Multicenter Retrospective Assessment of the German Study Group for Intraoperative Magnetic Resonance Imaging. Issue 6 (28th October 2015) - Coburger, Jan; Merkel, Andreas; Scherer, Moritz; Schwartz, Felix; Gessler, Florian; Roder, Constantin; Pala, Andrej; König, Ralph; Bullinger, Lars; Nagel, Gabriele; Jungk, Christine; Bisdas, Sotirios; et al.
Abstract: BACKGROUND: The ideal treatment strategy for low-grade gliomas (LGGs) is a controversial topic. Additionally, only smaller single-center series dealing with the concept of intraoperative magnetic resonance imaging (iMRI) have been published. OBJECTIVE: To investigate determinants for patient outcome and progression-free-survival (PFS) after iMRI-guided surgery for LGGs in a multicenter retrospective study initiated by the German Study Group for Intraoperative Magnetic Resonance Imaging. METHODS: A retrospective consecutive assessment of patients treated for LGGs (World Health Organization grade II) with iMRI-guided resection at 6 neurosurgical centers was performed. Eloquent location, extent of resection, first-line adjuvant treatment, neurophysiological monitoring, awake brain surgery, intraoperative ultrasound, and field-strength of iMRI were analyzed, as well as progression-free survival (PFS), new permanent neurological deficits, and complications. Multivariate binary logistic and Cox regression models were calculated to evaluate determinants of PFS, gross total resection (GTR), and adjuvant treatment. RESULTS: A total of 288 patients met the inclusion criteria. On multivariate analysis, GTR significantly increased PFS (hazard ratio, 0.44; P < .01), whereas "failed" GTR did not differ significantly from intended subtotal-resection. Combined radiochemotherapy as adjuvant therapy was a negative prognostic factor (hazard ratio: 2.84, P < .01). Field strength of iMRI was not associated with PFS. In the binary logistic regression model, use of high-field iMRI (odds ratio: 0.51, P < .01) was positively and eloquent location (odds ratio: 1.99, P < .01) was negatively associated with GTR. GTR was not associated with increased rates of new permanent neurological deficits. CONCLUSION: GTR was an independent positive prognostic factor for PFS in LGG surgery. Patients with accidentally left tumor remnants showed a similar prognosis compared with patients harboring only partially resectable tumors. Use of high-field iMRI was significantly associated with GTR. However, the field strength of iMRI did not affect PFS.